The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5267/j.ijdns.2019.5.002
|View full text |Cite
|
Sign up to set email alerts
|

Electrical energy demand forecasting model using artificial neural network: A case study of Lagos State Nigeria

Abstract: Electrical Energy is an essential commodity which significantly contributes to the economic development of any country. Many non-linear factors contribute to the final output of electrical energy demand. In order to efficiently predict electrical energy demand, many time-series analysis and multivariate techniques have been suggested. In order for these methods to accurately work, an enormous quantity of historical dataset is essential which sometimes are not available, inadequate and inaccurate. To overcome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…Cockburn, Henderson, and Stern [9] reported further that China was likely to be the largest beneficiary as it dominates the AI market in Asia-Pacific by as high as 70 percent. These findings concur with those that were established by Cohen [10], who held AI-enabled automated transportation responsible for this increase; or by De Backer, DeStefano, Menon, and Suh [11] who also confirmed that China was likely to embrace fleet-wide traffic flow through AI applications, hence elevating congestion levels [1,[12][13][14][15][16][17][18].…”
Section: Literature Reviewsupporting
confidence: 88%
“…Cockburn, Henderson, and Stern [9] reported further that China was likely to be the largest beneficiary as it dominates the AI market in Asia-Pacific by as high as 70 percent. These findings concur with those that were established by Cohen [10], who held AI-enabled automated transportation responsible for this increase; or by De Backer, DeStefano, Menon, and Suh [11] who also confirmed that China was likely to embrace fleet-wide traffic flow through AI applications, hence elevating congestion levels [1,[12][13][14][15][16][17][18].…”
Section: Literature Reviewsupporting
confidence: 88%
“…To forecast electricity demand, ANN, RNN, SVR, PSO, MARS, ARIMA, SARIMA, MCDA, Regression, and LAEP software methods were used in several studies [5,6,19,20]. In general, socio-economic indicators, such as GDP and GDP per capita, energy importsexports, unemployment percentage, inflation percentage, population, average winter temperature and average summer temperature, regional development factor, and monthly electricity consumption values are used as independent variables.…”
Section: Introductionmentioning
confidence: 99%
“…In general, socio-economic indicators, such as GDP and GDP per capita, energy importsexports, unemployment percentage, inflation percentage, population, average winter temperature and average summer temperature, regional development factor, and monthly electricity consumption values are used as independent variables. Abdulsalama and Babatundea [5] have forecasted Lagos State electrical energy demand using an Artificial Neural Network (ANN)-based method. To forecast the performance of the presented technique, the results have been compared with actual data.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the artificial intelligence models, ref. [13] developed a model for forecasting electrical demand using a neural network for Lagos State in Nigeria. The novel model is effective for energy forecasting due to its training capability.…”
Section: Introductionmentioning
confidence: 99%